IFN-λ Inhibits Drug-Resistant HIV Infection of Macrophages - Wang, Xu; Wang, He; Liu, Man-Qing; Li, Jie-Liang; Zhou, Run-Hong; Zhou, Yu; Wang, Yi-Zhong; Zhou, Wang; Ho, Wen-Zhe (Frontiers in Immunology, 2017)
Type III interferons (IFN-lambdas) have been demonstrated to inhibit a number of virus, including HIV. We further examined the anti-HIV effect of IFN-lambdas in macrophages. We found that IFN-lambdas synergistically enhanced anti-HIV activity of antiretrovirals (AZT, Efavirenz, Indinavir and Emfuviride) in infected macrophages. Importantly, IFN-lambdas could suppress HIV infection of macrophages with the drug-resistant strains, including AZT-resistant virus (A012) and RT inhibitor-resistant virus (TC49). Mechanistically, IFN-lambdas were able to induce the expression of several important anti-HIV cellular factors, including myxovirus resistance 2 (Mx2), a newly identified HIV post-entry inhibitor and tetherin, a restriction factor that blocks HIV release from infected cells. These observations provide additional evidence to support the potential use of IFN-lambads as a therapeutic agent for the treatment of HIV infection.